A multimethod paleointensity approach applied to the historical Xitle lava flows (Central Mexico): towards the accurate paleointensity determination - Juan Morales; Nayeli Pérez-Rodríguez; Avto Goguitchaichvili; Miguel Cervantes-Solano (Earth, Planets and Space, 2020)
Abstract An inclusive rock-magnetic and absolute paleointensity survey of the ~ 2-ka-old Xitle volcano (southerly Basin of Mexico) was undertaken to assess the faithfulness of the paleomagnetic log carried by fresh, widely exposed and well-preserved lava flows. Paleomagnetic samples from six lava flows were subjected to paleointensity analysis with a multi-method approach: the Thellier–Coe, IZZI, and multi-specimen methods. Overall mean flow PI values from flows 4–6 obtained by the Thellier-type methods used yielded 68.4 µT (σ = ± 5.6 µT), 63.9 µT (σ = ± 5.8 µT) and 61.5 µT (σ = ± 4.3 µT) for the TC, IZZI, and IZZI with CR correction methods, respectively. Although multi-specimen paleointensity results were, in general, lower than that obtained with the other methods for the same flows, that for Flow 5 (61.8 µT) was very similar to those obtained with the Thellier-type methods. Based on the results obtained, this lava flows sequence could correspond to two eruptive periods; one related with the Xitle volcano (flows 3–6), and another older (flows 1 and 2). The combined archeomagnetic dating of the different flows reinforces this hypothesis, as well as the multi-modal distribution for the age of the Xitle, proposed two decades ago. The application of stricter acceptance criteria and consideration of cooling-rate correction could slightly reduce the scattered observations. The multi-method approach employed under this study, combined with detailed rock-magnetic experiments, may definitively increase the accuracy of paleointensity determinations.